SUBJECTIVE AWARENESS OF TOURISM-AWARE GROUP IN MAINTAINING NATURAL CONSERVATION AT THE CEURACEU EUMBOEN TOURISM ATTRACTION, ALUE JANG VILLAGE, PASIE RAYA SUB-DISTRICT, ACEH JAYA REGENCY - Fitra Afriana; Nirzalin Nirzalin; Saifuddin Saifuddin (Master Program of Sociology, Universitas Malikussaleh,, 2022)
This study examines the subjective awareness of the Tourism-Aware Group in Maintaining Nature Conservation at the Ceuraceu Eumboen Tourism Object, Alue Jang Village, Pasie Raya Sub-District, Aceh Jaya Regency. The problem in this research is the subjective awareness of what drives the tourism conscious group in preserving nature, and how the subjective awareness of the tourism conscious group in maintaining the preservation of nature. The research method used in this study is a qualitative research method. In this study, the researcher used the thoughts of Max Weber about social action. The results of this research show that what encourages tourism-aware groups to preserve nature at the Ceuraceu Eumboen tourist attraction, first, is because the tourism-aware group's love for nature encourages them to preserve nature. Second, they are aware that the Ceuraceu Eumboen waterfall is one of the springs used to meet the needs of the local community. Third, the source of economic income through tourism businesses. Furthermore, the subjective awareness of tourism-aware groups in preserving nature is that they form rules resulting from the agreement of tourism-aware groups with local communities, then establish cooperation between tourism-aware groups, hold regular discussions about the importance of preserving forests for the sustainable life of fellow Pokdarwis groups, lastly outreach to the community. Keywords: Subjective Awareness, Tourism-Aware Group, Nature Conservation, and Ceuraceu Eumboen.